Between democracy and law : the amorality of secession - Closa, Carlos; Margiotta, Costantino, 1972-; Martinico, Giuseppe; Routledge (Firm) (New York : Routledge, 2019)
This volume purports to explore the legal and political issues triggered by the new wave of secessionism. More specifically, those issues concern the interplay between notions of democracy (and democratic ends and means) and law (and the rule of law and constitutionalism). Against this background, the editors use amorality in order to escape the terrain of the justification of secession by making a distinction between the democratic theory of secession and the theory of democratic secession. In the first section, the theoretical nexus democracy-secession has been approached both from a legal and political theory perspective. The second section of the book examines the instruments that the theory of democratic secession invokes in order to justify secession and presents both legal and political science contributions. The third section focuses on social movements and political actors. The fourth section focuses on two case studies due to the awareness of the importance of the difference between secession in a democratic occidental context (which call into play the discussion of the democratic theories) and separations in a non-democratic context (where the nexus between secession and democracy is not really central).
Introduction / Closa, Margiotta, Martinico -- An update on secession as the 'Ultimate Right': For a liminal legality / Margiotta -- Secession V forceful union. A provisional enquiry into the right to decide to secede and the obligation to belong / Bengoextea -- A critique of the theory of democratic secession / Closa -- Decide on what? Addressing secessionist claims in an interdependent Europe innerarity / Errasti -- Constitutionalists' guide to the populist challenge: Lessons from Canada / Martinico -- Sovereignty referendums: A question of majority? -- Or how 'Majority' actually begs numerous questions / Beulac -- Independence referendums. History, legal status and voting behaviour / Qvortrup -- The framing of secessionism in the neo-liberal crisis: The Scottish and Catalan cases / Della Porta, O'Connor, Portos -- The Europeanization of the Catalan debate: A "War of Attrition"? / Guidi, Casula -- On Brexit and secession(s) / Skoutaris -- An attempt to disentangle the Crimean impasse / Crema.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Secession; Separatist movements -- Case studies; Constitutional law; LAW / General; LAW / Administrative Law & Regulatory Practice; LAW / Civil Rights